Resin composition containing metal organic structure and dispersion liquid
By adding a metal organic structure with a ring-shaped or cage-shaped structure and a dispersant to the resin, the problem of difficult to disperse the metal organic structure in the resin is solved, and its adsorption performance is significantly improved.
Patent Information
- Application Number
- CN202380038167.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-26
- Filing Date
- 2023-05-02
- Publication Date
- 2024-12-13
AI Technical Summary
The powdered metal organic structure is difficult to disperse uniformly in the resin, resulting in the inability to fully exert its excellent adsorption properties.
Add a metal organic structure with a cyclic or cage-like structure and a dispersant, such as polyvinyl alcohol, amino acid or phosphoric acid, to the resin, to uniformly disperse the metal organic structure by optimizing the ratio of metal ions and organic ligands.
The uniform dispersion of metal organic structures in the resin is achieved, which significantly improves its adsorption performance.
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition and a dispersion containing a metal organic structure, and more particularly to a resin composition and a dispersion in which the metal organic structure is uniformly dispersed in a resin or a dispersion medium and can exhibit the excellent adsorption performance of the metal organic structure. Background Art
[0002] Metal-organic frameworks (MOFs) composed of a central metal and multidentate organic ligands coordinated thereto are porous three-dimensional structures formed by the aggregation of metal complexes composed of a central metal and organic ligands. Compared with other porous materials such as zeolites or activated carbon, the pores of metal-organic frameworks can be easily designed with a pore diameter or a space inside the pores, and have pores with uniform pore diameters, so the use of metal-organic frameworks as adsorbents has been proposed.
[0003] For example, in the following Patent Document 1, a transparent gas barrier water-absorbing laminate is proposed, which has a substrate layer and a sealant layer, the substrate layer contains a transparent gas barrier film, the sealant layer contains a water absorbent and a heat-sealable resin, the water absorbent contains an inorganic water absorbent and / or an organic water absorbent, the content of the water absorbent in the layer containing the water absorbent is 0.5% by mass or more and 70% by mass or less, and an organic metal structure as one of the above-mentioned inorganic water absorbents can be used.
[0004] In addition, the following Patent Document 2 proposes a composition containing a thermoplastic resin and a gas absorbent, wherein the gas absorbent contains a gas physical absorbent and / or a gas chemical absorbent, and the gas physical absorbent has a BET specific surface area of 50 m 2 / g or more, 4000m 2 / g or less, the content of the gas absorbent in the layer containing the gas absorbent is 0.5 mass % to 30 mass %, and in the gas absorbent film, a metal structure as one of the gas physical absorbents can be used. Prior art literature Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2021-53946 Patent Document 2: Japanese Patent Application Publication No. 2021-54490 Summary of the invention Problems to be solved by the invention
[0006] In the above-mentioned Patent Documents 1 and 2, a specific metal organic structure such as copper trimesate, iron trimesate, aluminum terephthalate, 2-methylimidazole zinc, etc. is blended with a thermoplastic resin as an inorganic water absorbent or a gas physical absorbent. However, it is generally not easy to uniformly disperse a powdered metal organic structure in a resin, and sometimes aggregates exist in a film or the like obtained from a resin composition containing the metal organic structure. In this case, the excellent adsorption performance of the metal organic structure may not be fully utilized.
[0007] Therefore, an object of the present invention is to provide a resin composition and a dispersion liquid containing a metal organic structure, wherein the metal organic structure is uniformly dispersed in a resin or a dispersion medium and can exhibit the excellent adsorption performance of the metal organic structure. Solutions for solving problems
[0008] According to the present invention, a resin composition is provided, characterized in that the resin contains a metal organic structure and a dispersant, wherein the metal organic structure is a metal organic structure having a ring structure or a cage structure formed by coordination of at least one organic ligand and at least one metal ion.
[0009] In the resin composition of the present invention, it is preferred that: (1) the dispersant is at least one selected from polyvinyl alcohol, amino acid, phosphoric acid, and polyallylamine; (2) the content ratio (mass ratio) of the metal organic structure to the dispersant is 1:1 to 1:10; (3) the metal organic structure contains at least one zinc ion as the metal ion and the organic ligand is composed of a compound having an imidazole skeleton; (4) the compound having an imidazole skeleton is 2-methylimidazole; (5) the metal organic structure contains at least one alkali metal ion as the metal ion and the organic ligand is composed of a cyclodextrin compound; (6) the alkali metal ion is a potassium ion; (7) the cyclodextrin compound is α-cyclodextrin or γ-cyclodextrin; (8) the metal organic structure contains at least one copper ion as the metal ion and the organic ligand is composed of a compound having a monocyclic or polycyclic skeleton; (9) the compound having a monocyclic or polycyclic skeleton is trimesic acid.
[0010] According to the present invention, there is also provided a dispersion liquid, characterized in that it contains a metal organic structure and a dispersant, wherein the metal organic structure is a ring-shaped or cage-shaped metal organic structure formed by coordination of at least one organic ligand and at least one metal ion.
[0011] In the dispersion of the present invention, it is preferred that: (1) the dispersant is at least one selected from polyvinyl alcohol, amino acid, phosphoric acid, and polyallylamine; (2) the content ratio (mass ratio) of the metal organic structure to the dispersant is 1:1 to 1:30; (3) the dispersion medium is water and / or an alcohol solvent; (4) the metal organic structure contains at least one metal ion that is a zinc ion and the organic ligand that is composed of a compound having an imidazole skeleton; (5) the compound having an imidazole skeleton is 2-methylimidazole; (6) the metal organic structure contains at least one metal ion that is an alkali metal ion and the organic ligand that is composed of a cyclodextrin compound; (7) the alkali metal ion is a potassium ion; (8) the cyclodextrin compound is α-cyclodextrin or γ-cyclodextrin; (9) the metal organic structure contains at least one metal ion that is a copper ion and the organic ligand that is composed of a compound having a monocyclic or polycyclic skeleton; (10) the compound having a monocyclic or polycyclic skeleton is trimesic acid. Effects of the Invention
[0012] In the resin composition and dispersion of the present invention, by incorporating a specific dispersant into the resin or dispersion medium together with the metal organic structure, the metal organic structure can be uniformly dispersed in the resin or dispersion without agglomerating, and the resin composition and dispersion can exhibit the excellent adsorption performance of the metal organic structure. DETAILED DESCRIPTION
[0013] (Metal-organic structures) The metal organic structure contained in the resin composition and dispersion of the present invention has a porous crystal structure of a ring structure or a cage structure formed by coordination of at least one organic ligand and at least one metal ion. Since the spatial structure inside the crystal is uniform, it can effectively enclose guest molecules, thereby exhibiting excellent adsorption performance. It should be noted that in this specification, the ring structure or cage structure of the metal organic structure is defined as a cage structure, which is a cubic crystal structure obtained by further crystallizing the metal organic structure having a ring structure, wherein metal ions are used as linking groups of organic ligands.
[0014] The metal ions used in the metal organic structure may be, but are not limited to, metal ions that can form coordination bonds with organic ligands. Examples include metal ions such as Li, Na, K, Rb, Be, Mg, Ca, Sr, Ba, Sc, Y, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mn, Re, Fe, Ru, Os, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, Zn, Cd, Hg, Al, Ga, In, Tl, Si, Ge, Sn, Pb, As, Sb, and Bi, and at least one of them can be selected.
[0015] As the organic ligand, any compound that can form a coordination bond with a metal ion can be used, and a compound having a functional group that can form a coordination bond with a metal can be used. Examples of such functional groups include hydroxyl, imidazole, pyridyl, carboxyl, sulfonic acid, and amide groups. Specifically, as the organic ligand, an organic compound having a cyclic structure can be used, which can encapsulate the guest molecule. As such an organic ligand, a cyclodextrin compound can be cited. As the cyclodextrin compound, α-cyclodextrin, β-cyclodextrin, and γ-cyclodextrin can be exemplified, among which α-cyclodextrin and γ-cyclodextrin can be preferably used. In addition, as organic ligands, compounds having imidazole skeletons such as imidazole, 2-methylimidazole, and 2-formylimidazole, compounds having monocyclic or polycyclic skeletons such as terephthalic acid and trimesic acid, etc. can also be used. These compounds are not compounds that can enclose guest molecules by themselves like the above-mentioned organic compounds having a cyclic structure, but can coordinately bond with metal ions to form metal organic structures having a cyclic structure or a cage structure that can enclose guest molecules.
[0016] Specific examples of the metal organic structure that can be preferably used in the resin composition and dispersion of the present invention include the following. It is preferred to use a metal organic structure in which the metal ion is zinc ion and the organic ligand is a compound having an imidazole skeleton, especially a metal organic structure in which the organic ligand is 2-methylimidazole (ZIF-8); a metal organic structure in which the metal ion is an alkali metal ion and the organic ligand is a cyclodextrin compound, especially a metal organic structure in which the metal ion is potassium ion and the organic ligand is α-cyclodextrin or γ-cyclodextrin (α-CDMOF or γ-CDMOF); a metal organic structure in which the metal ion is copper ion and the organic ligand is a compound having a monocyclic or polycyclic skeleton, especially a metal organic structure in which the organic ligand is trimellitic acid (C-300). In the present invention, CDMOF can also be preferably used among the above metal organic structures.
[0017] Among the metal-organic structures (CDMOFs) in which the organic ligand is a cyclodextrin compound and the metal ion is a potassium ion, which can be suitably used in the resin composition and dispersion liquid of the present invention, the metal-organic structure in which the cyclodextrin compound is bonded in the range of 0.05 to 0.8 moles per 1 mole of potassium ions is suitable in terms of exhibiting excellent adsorption performance.
[0018] (Method for producing metal organic structure) The metal organic structure used in the present invention may be a conventionally known commercially available metal organic structure, and can be produced by the following method. That is, a first aqueous solution containing metal ions and organic ligands capable of coordinating with the metal ions is prepared, and then a second solvent containing an organic solvent is added to the first aqueous solution, thereby generating a metal organic structure in which the organic ligands coordinate with the metal ions. In the first aqueous solution, the metal compound supplying the metal ion is not limited thereto, and examples thereof include metal hydroxides, inorganic halide salts such as chloride salts, inorganic acid salts such as nitrates and acetates, etc. Specifically, when the metal ion is an alkali metal ion, an alkali metal hydroxide is preferably used, and when the metal ion is a Zn ion or a Fe ion, an inorganic acid salt is preferably used.
[0019] In the first aqueous solution, the amount of the organic ligand is preferably in the range of 0.05 to 50 mol, more preferably in the range of 0.1 to 40 mol, and more preferably in the range of 0.125 to 30 mol, relative to 1 mol of the metal ion. When the metal ion is an alkali metal ion, the amount of the organic ligand is preferably in the range of 0.05 to 8 mol, particularly preferably in the range of 0.125 to 0.8 mol, based on 1 mol of the metal ion. When the metal ion is a Zn ion, the amount of the organic ligand is in the range of 0.5 to 50 mol, particularly preferably in the range of 15 to 40 mol, based on 1 mol of the Zn ion. Furthermore, when the metal ion is an Fe ion, the amount of the organic ligand is preferably in the range of 0.05 to 5 mol, and particularly preferably in the range of 0.1 to 1 mol, relative to 1 mol of the Fe ion.
[0020] The amount of water in the first aqueous solution is preferably in the range of 10 to 5000 mol relative to 1 mol of metal ions. When the metal ions are alkali metal ions, the amount of water is preferably in the range of 50 to 200 mol relative to 1 mol of metal ions, and particularly preferably in the range of 100 to 150 mol. The molar ratio of the organic ligand to water (organic ligand: water) is preferably in the range of 1:10 to 1:2000, and particularly in the case where the organic ligand is a cyclodextrin compound, it is preferably in the range of 1:100 to 1:1300.
[0021] The second solution added to the first aqueous solution prepared as described above is preferably a solution capable of reducing the pH of the first aqueous solution, and preferably an organic solvent capable of deprotonating the coordination bonding site of the organic ligand is used. The organic ligand is deprotonated to form a coordination bond with the metal ion, thereby forming a metal organic structure. Examples of such an organic solvent include at least one solvent selected from alcohol solvents such as methanol, ethanol, 1-propanol, and 1-butanol, ketone solvents such as acetone, and aprotic solvents such as N,N-dimethylformamide. Among them, alcohol solvents are preferred, and methanol is particularly preferred. The organic solvent is preferably added in an amount of 3 to 1000 mol, particularly 5 to 500 mol, relative to 1 mol of the metal ion. In particular, when the metal ion is potassium ion and the organic ligand is α-cyclodextrin, it is appropriate to add the organic solvent in an amount of 10 to 400 mol, preferably 50 to 300 mol, and more preferably 100 to 200 mol relative to 1 mol of the potassium ion. In the case of γ-cyclodextrin, it is appropriate to add the organic solvent in an amount of 3 to 100 mol, preferably 5 to 50 mol, and more preferably 10 to 30 mol relative to 1 mol of the potassium ion.
[0022] When adding the second solution to the first aqueous solution, it is preferred to stir the first aqueous solution while adding the second solution for 1 to 20 minutes, preferably 10 to 15 minutes. If the second solution is added all at once, it is possible to produce turbidity and fail to obtain the desired metal organic structure, but by adding the second solution for a period of time within the above range, a nucleus can be formed, the crystal structure grows, and the desired metal organic structure is easily obtained. The method of adding is not limited to this, and examples include a method of adding at a certain speed using a dropping funnel, a method of adding a certain amount at regular intervals, and a method of adding by changing the amount of addition obliquely. After the addition of the second solution is completed, the mixed solution is preferably stirred at room temperature for 5 to 50 hours, preferably 10 to 30 hours. The generated metal organic structure is separated by filtration, etc., washed with an organic solvent such as methanol as needed, and then dried to remove the organic solvent and water, so that a powder of a metal organic structure with a ring structure or a cage structure can be obtained.
[0023] (Dispersant) In the resin composition and dispersion of the present invention, as a dispersant added to improve the dispersibility of the metal organic structure in the resin or dispersion, at least one selected from water-soluble polymers such as polyvinyl alcohol, amino acid compounds composed of α-amino acids such as glycine, lysine, and aspartic acid, phosphoric acid compounds such as orthophosphoric acid, metaphosphoric acid, and polyphosphoric acid, polyamine compounds such as polyallylamine, etc. can be used. Among them, polyvinyl alcohol, amino acids, phosphoric acid, and polyallylamine can be preferably used.
[0024] (Resin composition) The resin composition of the present invention is a composition comprising the above-mentioned metal organic structure and a dispersant in a resin. As the resin containing the metal organic structure, conventionally known resins can be used, but are not limited thereto, and examples thereof include low-, medium-, and high-density polyethylene, linear low-density polyethylene, linear ultra-low-density polyethylene, isotactic polypropylene, syndiotactic polypropylene, propylene-ethylene copolymers, polybutene-1, ethylene-butene-1 copolymers, propylene-butene-1 copolymers, ethylene-propylene-butene-1 copolymers and other olefin resins, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate and other polyester resins, nylon 6, nylon 6,6, nylon 6,10 and other polyamide resins, polycarbonate resins and other thermoplastic resins, phenolic resins, epoxy resins, polyurethane resins, melamine resins, urea resins, alkyd resins, unsaturated polyester resins, silicone resins and other thermosetting resins, or photocurable acrylic resins, etc. In the resin composition of the present invention, in order for the metal organic structure in the resin composition to efficiently exhibit adsorption performance, the resin as the matrix is preferably a resin having excellent gas permeability, and low-density polyethylene is particularly preferably used among the above resins.
[0025] In the resin composition, the content of the metal organic structure varies depending on the type of metal organic structure used, the purpose, etc., and cannot be generalized, but is preferably contained in an amount of 0.01 to 50 parts by mass, particularly preferably 0.05 to 10 parts by mass, relative to 100 parts by mass of the resin. When the amount of the metal organic structure is less than the above range, the desired adsorption may not be obtained, while when the amount of the metal organic structure is greater than the above range, the moldability when the resin composition is molded into a desired form may be impaired. In addition, the content ratio (mass ratio) of the metal organic structure to the dispersant in the resin composition is preferably 1: 1 to 1: 10, and particularly preferably 1: 3 to 1: 8. When the content of the dispersant is less than the above range, it is difficult to sufficiently improve the dispersibility of the metal organic structure compared to when it is within the above range. On the other hand, when the content of the dispersant is more than the above range, the moldability when the resin composition is molded into a desired form may be impaired. The resin composition may contain conventionally known additives for resins such as an antioxidant and a filler in addition to the above-mentioned metal organic structure and dispersant.
[0026] The preparation of the resin composition can be carried out by a conventionally known method, but is not limited thereto. It can be prepared by a method of dry-mixing the metal organic structure and the dispersant with the resin, a method of adding the metal organic structure and the dispersant to the resin in a molten state and mixing them, etc. However, by using a dispersion containing the metal organic structure and the dispersant of the present invention described later, adding the dispersion to the resin in a molten state and melt-kneading, a resin composition in which the metal organic structure is uniformly dispersed in the resin can be efficiently prepared.
[0027] The resin composition of the present invention can be molded into various forms depending on its application, and can be molded into forms such as cups, trays, bottles, and tubes in addition to pellets, films, and sheets.
[0028] (Dispersion liquid) The dispersion of the present invention is a dispersion in which the above-mentioned metal organic structure and a dispersant are uniformly dispersed in a dispersion medium. Examples of the dispersion medium used in the dispersion include water, alcohol solvents such as methanol, ethanol, and isopropanol, ketone solvents such as 2-butanone and acetone, and aromatic solvents such as toluene. In particular, water and / or alcohol solvents are preferably used.
[0029] The content of the metal organic structure in the dispersion varies depending on the type of the metal organic structure and dispersion medium used, the content of the dispersant, etc., and cannot be generalized, but is contained in the range of 0.01 to 30 g / L, particularly 10 to 20 g / L. When the amount of the metal organic structure is less than the above range, the desired adsorption may not be obtained, and the workability when added to the resin may be deteriorated compared to the case within the above range. On the other hand, when the amount of the metal organic structure is more than the above range, it may be difficult to uniformly disperse the metal organic structure compared to the case within the above range. In addition, the content ratio (mass ratio) of the metal organic structure to the dispersant in the dispersion is preferably 1: 1 to 1: 30, and particularly preferably 1: 5 to 1: 20. When the content of the dispersant is less than the above range, it is difficult to sufficiently improve the dispersibility of the metal organic structure compared to the case within the above range. On the other hand, even if the content of the dispersant is more than the above range, further improvement of the dispersibility is expected, but the operability of the dispersion may be impaired.
[0030] The preparation of the dispersion is not limited thereto and can be carried out by the following method: That is, a dispersant is added to a solvent and stirred to prepare a dispersant-containing solution in advance, and the metal organic structure is added to the dispersant-containing solution and dispersed to prepare a dispersion in which the metal organic structure is uniformly dispersed. The dispersion treatment is preferably carried out by a stirring method using a stirring rod, a stirring stone or the like, but may also be carried out using a dispersing machine such as an ultrasonic disperser, a homogenizer, or a mixer.
[0031] The dispersion of the present invention itself can be used as an adsorbent or the like, but can also be preferably used for the preparation of a resin composition containing the above-mentioned metal organic structure. Example
[0032] Hereinafter, in order to explain the present invention in more detail, examples performed by the present inventors will be described.
[0033] (Measurement method) [Adsorption test of adsorbent-containing resin composition] 2 g of the resin composition was filled into a flask filled with 200 ppm of octane to prepare an adsorption sample. The gas component concentration was measured using the following detector tube 1 hour after the adsorption sample was filled. Octane concentration: detection tube (Gastec, No. 105). [Evaluation method for temporal stability in dispersion liquid] The state of the dispersion was visually checked 30 minutes and 3 days after preparation. If there was no precipitation after 3 days, it was rated as ○ (high temporal stability), if there was precipitation after 30 minutes to 3 days, it was rated as Δ (moderate temporal stability), and if there was precipitation after 30 minutes, it was rated as × (low temporal stability).
[0034] <Preparation of resin composition> (Example 1) The following raw materials were mixed to obtain a resin composition containing an adsorbent. LDPE (Novatec LC600A): 93.3 parts. Polyallylamine (PAA: average molecular weight MW5000): 6.0 parts. ZIF-8 (manufactured by Aldrich): 0.7 parts. Then, 1 g of the resin composition prepared above was formed into a film having an average film thickness of 0.2 mm using a press. After drying the prepared film at 140°C for 3 hours, 1 g of the film was filled into a flask filled with 200 ppm octane to prepare an adsorption sample. The gas component concentration was measured by a detector tube 1 hour after the adsorption sample was filled. The adsorption test showed that the film formed by the resin composition containing the gas adsorbent adsorbed 200 ppm octane.
[0035] (Comparative Example 1) The following materials were mixed to obtain a resin composition. LDPE (Novatec LC600A): 100 parts. Then, 1 g of the resin composition prepared above was formed into a film having an average film thickness of 0.2 mm using a press. The adsorption measurement test was carried out in the same manner as in Example 1, and the membrane adsorbed 20 ppm of octane.
[0036] (Comparative Example 2) The following materials were mixed to obtain a resin composition. LDPE (Novatec LC600A): 94.0 parts. PAA: 6.0 parts. Then, 1 g of the resin composition prepared above was formed into a film having an average film thickness of 0.2 mm using a press. The adsorption measurement test was carried out in the same manner as in Example 1, and the membrane adsorbed 45 ppm of octane.
[0037] <Preparation of dispersion> (Example 2) 2 parts by mass of PAA as a dispersant and 1 part by mass of ZIF-8 as a metal organic structure were added to 88 parts by mass of pure water, and the mixture was stirred at room temperature for 10 minutes, thereby obtaining a dispersion A. The temporal stability of the dispersion A was evaluated as ○.
[0038] (Example 3) A dispersion B was obtained in the same manner as in Example 2 except that the composition ratio (parts by mass) was pure water:PAA:ZIF-8=88:5:1. The temporal stability of the dispersion liquid B was evaluated as ○.
[0039] (Example 4) A dispersion C was obtained in the same manner as in Example 2 except that the composition ratio (parts by mass) was pure water:PAA:ZIF-8=88:10:1. The temporal stability of the dispersion C was evaluated as ○.
[0040] (Example 5) A dispersion D was obtained in the same manner as in Example 2 except that the composition ratio (parts by mass) was pure water:PAA:ZIF-8=88:20:1. The temporal stability of the dispersion D was evaluated as Δ.
[0041] (Example 6) A dispersion E was obtained in the same manner as in Example 2 except that the dispersant was polyvinyl alcohol (PVA: average molecular weight MW 900-1100) and the composition ratio (parts by mass) was pure water:PVA:ZIF-8=169:1.7:1. The temporal stability of the dispersion E was evaluated as Δ.
[0042] (Example 7) Dispersion liquid F was obtained in the same manner as in Example 2 except that glycine was used as the dispersant and the composition ratio (parts by mass) was changed to pure water:glycine:ZIF-8=298:33:1. The temporal stability of the dispersion F was evaluated as ○.
[0043] (Example 8) Dispersion liquid G was obtained in the same manner as in Example 2 except that lysine was used as the dispersant and the composition ratio (parts by mass) was changed to pure water:lysine:ZIF-8=298:33:1. The temporal stability of the dispersion G was evaluated as Δ.
[0044] (Example 9) Dispersion liquid H was obtained in the same manner as in Example 2 except that magnesium aspartate was used as the dispersant and the composition ratio (parts by mass) was changed to pure water:magnesium aspartate:ZIF-8=298:33:1. The temporal stability of the dispersion H was evaluated as Δ.
[0045] (Example 10) A dispersion liquid I was obtained in the same manner as in Example 2 except that phosphoric acid was used as the dispersant and the composition ratio (parts by mass) was changed to pure water:phosphoric acid:ZIF-8=356:2.7:1. The temporal stability of the dispersion liquid I was evaluated as ○.
[0046] (Example 11) Dispersion liquid J was obtained in the same manner as in Example 4 except that the dispersant was PAA and the metal organic structure was α-CDMOF. The temporal stability of the dispersion J was evaluated as ○. It should be noted that the preparation of α-CDMOF was carried out as follows. After adding pure water to a 150 ml container (mayonnaise bottle), potassium hydroxide is added to the container and dissolved at room temperature. α-cyclodextrin is further added and dissolved at room temperature. Next, methanol is added dropwise over about 15 minutes while stirring the solution with a stirrer. After addition, the solution is stirred for 24 hours to obtain a suspension containing a solid product. The solid product is filtered out from the obtained suspension, and the separated solid product is washed with methanol. After washing, the solid product is dried at 50°C overnight to obtain the α-CDMOF of Example 11. The molar ratio of the components used is potassium ion: α-cyclodextrin: water: methanol = 1: 0.125: 137.5: 184.
[0047] (Example 12) A dispersion K was obtained in the same manner as in Example 6 except that the dispersant was PVA and the metal organic structure was the above-mentioned α-CDMOF. The temporal stability of the dispersion K was evaluated as ○.
[0048] (Example 13) A dispersion liquid L was obtained in the same manner as in Example 8 except that lysine was used as the dispersant and the above-mentioned α-CDMOF was used as the metal organic structure. The temporal stability of the dispersion L was evaluated as ○.
[0049] (Example 14) A dispersion liquid M was obtained in the same manner as in Example 9 except that the dispersant was magnesium aspartate and the metal organic structure was the above-mentioned α-CDMOF. The temporal stability of the dispersion liquid M was evaluated as ○.
[0050] (Example 15) Dispersion liquid N was obtained in the same manner as in Example 4 except that the dispersant was made PAA and the metal organic structure was made γ-CDMOF. The temporal stability of the dispersion N was evaluated as ○. It should be noted that the preparation of γ-CDMOF was carried out according to the following method. After adding pure water to a 150 ml container (mayonnaise bottle), potassium hydroxide is added to the container and dissolved at room temperature. α-cyclodextrin is further added and dissolved at room temperature. Next, methanol is added dropwise over about 15 minutes while stirring the solution with a stirrer. After addition, the solution is stirred for 24 hours to obtain a suspension containing a solid product. The solid product is filtered out from the obtained suspension, and the separated solid product is washed with methanol. After washing, the solid product is dried at 50°C overnight to obtain the γ-CDMOF of Example 15. The molar ratio of the components used is potassium ion: γ-cyclodextrin: water: methanol = 1: 0.125: 137.5: 20.
[0051] (Example 16) A dispersion liquid O was obtained in the same manner as in Example 6 except that the dispersant was PVA and the metal organic structure was the above-mentioned γ-CDMOF. The temporal stability of the dispersion O was evaluated as ○.
[0052] (Example 17) A dispersion liquid P was obtained in the same manner as in Example 7 except that glycine was used as the dispersant and the above-mentioned γ-CDMOF was used as the metal organic structure. The temporal stability of the dispersion liquid P was evaluated as ○.
[0053] (Example 18) A dispersion Q was obtained in the same manner as in Example 8 except that lysine was used as the dispersant and the γ-CDMOF was used as the metal organic structure. The temporal stability of the dispersion liquid Q was evaluated as ○.
[0054] (Example 19) A dispersion R was obtained in the same manner as in Example 9 except that the dispersant was magnesium aspartate and the metal organic structure was the above-mentioned γ-CDMOF. The temporal stability of the dispersion R was evaluated as ○.
[0055] (Example 20) A dispersion liquid S was obtained in the same manner as in Example 7 except that glycine was used as the dispersant and C300 (manufactured by Aldrich Corporation) was used as the metal organic structure. The temporal stability of the dispersion S was evaluated as ○.
[0056] (Example 21) A dispersion liquid T was obtained in the same manner as in Example 8 except that lysine was used as the dispersant and C300 (manufactured by Aldrich Corporation) was used as the metal organic structure. The temporal stability of the dispersion T was evaluated as ○.
[0057] (Example 22) A dispersion U was obtained in the same manner as in Example 9 except that magnesium aspartate was used as the dispersant and C300 (manufactured by Aldrich Corporation) was used as the metal organic structure. The temporal stability of the dispersion U was evaluated as ○.
Claims
1. A resin composition, characterized in that The resin contains a metal organic structure and a dispersant. The metal organic structure is a metal organic structure having a ring structure or a cage structure formed by coordination of at least one organic ligand and at least one metal ion.
2. The resin composition according to claim 1, wherein The dispersant is at least one selected from polyvinyl alcohol, amino acid, phosphoric acid, and polyallylamine.
3. The resin composition according to claim 1, wherein The content ratio, ie, the mass ratio, of the metal organic structure to the dispersant is 1:1 to 1:
10.
4. The resin composition according to claim 1, wherein The metal organic structure at least contains a zinc ion as the metal ion and a compound having an imidazole skeleton as the organic ligand.
5. The resin composition according to claim 4, wherein The compound having an imidazole skeleton is 2-methylimidazole.
6. The resin composition according to claim 1, wherein The metal-organic structure at least contains an alkali metal ion as the metal ion and a cyclodextrin compound as the organic ligand.
7. The resin composition according to claim 6, wherein The alkali metal ion is a potassium ion.
8. The resin composition according to claim 6, wherein The cyclodextrin compound is α-cyclodextrin or γ-cyclodextrin.
9. The resin composition according to claim 1, wherein The metal-organic structure at least contains copper ions as the metal ions and a compound having a monocyclic or polycyclic skeleton as the organic ligand.
10. The resin composition according to claim 9, wherein The compound having a monocyclic or polycyclic skeleton is trimesic acid.
11. A dispersion, characterized in that: The invention comprises a metal organic structure and a dispersant, wherein the metal organic structure is a ring-shaped or cage-shaped metal organic structure formed by coordination of at least one organic ligand and at least one metal ion.
12. The dispersion according to claim 11, wherein The dispersant is at least one selected from polyvinyl alcohol, amino acid, phosphoric acid, and polyallylamine.
13. The dispersion according to claim 11, wherein The content ratio of the metal organic structure to the dispersant, ie the mass ratio, is 1:1 to 1:
30.
14. The dispersion according to claim 11, wherein The dispersion medium is water and / or an alcohol solvent.
15. The dispersion according to claim 11, wherein The metal organic structure at least contains a zinc ion as the metal ion and a compound having an imidazole skeleton as the organic ligand.
16. The dispersion according to claim 15, wherein The compound having an imidazole skeleton is 2-methylimidazole.
17. The dispersion according to claim 11, wherein The metal-organic structure at least contains an alkali metal ion as the metal ion and a cyclodextrin compound as the organic ligand.
18. The dispersion according to claim 17, wherein The alkali metal ion is a potassium ion.
19. The dispersion according to claim 17, wherein The cyclodextrin compound is α-cyclodextrin or γ-cyclodextrin.
20. The dispersion according to claim 11, wherein The metal-organic structure at least contains copper ions as the metal ions and a compound having a monocyclic or polycyclic skeleton as the organic ligand.
21. The dispersion according to claim 20, wherein The compound having a monocyclic or polycyclic skeleton is trimesic acid.
